Validation and Determination of Quinolizidine Alkaloids (QAs) in Lupin Products by Gas Chromatography with Flame Ionization Detection (GC-FID). (3rd March 2020) - Lee, Hae-Won; Hwang, In-Min; Lee, Hee Min; Yang, Ji-Su; Park, Eun Jin; Choi, Jae Won; Seo, Hye Young; Kim, Sung Hyun
Abstract: Products of lupin, a leguminous plant belonging to genus Lupinus, have high protein contents and are consumed in Mediterranean and Middle East countries. However, quinolizidine alkaloids (QAs) present in lupin have been reported to be toxic for humans and animals. Therefore, we carried out a quantitative determination of the QAs such as sparteine, angustifoline, lupanine, and 13-hydroxylupanine, which are known to be the major components in lupin and lupin products. The QAs were determined in three lupin products, namely, lupin beans, lupin cookies, and a lupin drink. The analysis was carried out using gas chromatography with a flame ionization detector (GC-FID) and the method was also validated. All of the QAs were eluted in 20 min, and the correlation coefficients were acceptable ( R 2 > 0.99). The limit of quantification in this method was lower than for a previously used capillary electrophoresis–mass spectrometric method. The total QA contents in lupin beans, lupin cookies, and lupin drink were 97.031, 4.786, and 67.887 µg/mL. Based on our results, it was concluded that these products were safe for consumption. It is believed that this method can be effectively used for the determination of QAs as GC-FID is a widely used technique.